Floating microplastics and aggregate formation in the Western Mediterranean Sea. (March 2019) - de Haan, William P.; Sanchez-Vidal, Anna; Canals, Miquel; ,
Abstract: Pollution by large-sized plastics and microplastic debris is widespread in all Earth environments, also threatening marine ecosystems worldwide. In this study we determine the load of microplastics in the Western Mediterranean Sea and evaluate their aggregation potential into marine aggregates. We report average microplastic abundances of 0.10 ± 0.09 items m −2 (max: 0.50 items m −2 ). Abundances and chemical composition of microplastics are subject to temporal changes as a function of human activities in the areas of influence and shifting meteorological and sea-state conditions. We find that microplastics were on average smaller in mass than other studies conducted in the Mediterranean Sea indicating longer exposure times in the environment. The microplastic aggregation potential was determined by inspecting formed biogenic aggregates either during sample collection or in the laboratory. Smaller and more angular microplastics dominated in marine aggregates, representing an average 40% in abundance and 25% in mass of microplastics. Highlights: Microplastic concentrations averaged 0.10 ± 0.09 items m −2 and 0.03 ± 0.02 mg m −2 . Reduced sizes and mass of microplastics were found in relation to other studies. 40% in abundance and 25% in mass of microplastics incorporated into aggregates. Marine aggregates would behave both as floats and ballasts for microplastics.